There is techne and phronesis in movement: A beautiful combination for health and well-being! - Maria Kosma (Turkish Journal of Kinesiology)
Drawing on Aristotle’s concepts of techne (art or craft) and phronesis (practical wisdom), the purpose of this concept-based article was to showcase that there is techne and phronesis in movement, including their interrelations for the long-lasting love of movement, and thus health and well-being. The paper is divided into four sections. In the first section, the researcher exemplifies the embodied movement of art (techne) emphasizing skill mastery. Movement is both techne and action – a holistic process encompassing sensations of strength, physicality, and mental clarity. In the second section, the researcher emphasizes how wisdom in decision making (phronesis) can lead to active lifestyles via the use of praxis vs. theoria. The links between techne and phronesis are discussed in the third section, whereby skill mastery (techne) can facilitate phronetic action regarding active and healthy lifestyles. This process is exemplified in performing arts, including dancing, aerial dancing, and physical theater. Lastly, implications for movement programming are offered, emphasizing the importance of a strong physical culture to achieve the techne of movement and thus wisdom in decision making about living the good life. There is techne and phronesis in movement, which is a beautiful and powerful combination for health and well-being.